Orthodontic-Surgical Management of Impacted Maxillary Central Incisor Related to Supernumerary Tooth: a Case Report - Rai, Amita; Giri, Jamal; Sah, Barun Kumar; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha (Journal of BP Koirala Institute of Health Sciences, 2023)
Anterior teeth play an important role in maintaining esthetics and phonetics in human beings. Missing anterior teeth might result in rotation, shifting, and root resorption of the adjacent teeth, loss of eruption space, underdevelopment of the anterior part of the maxilla, and crossbite. Adolescent patients are very conscious about how they look, and missing anterior teeth lowers their selfesteem. Due to the above reasons, missing anterior teeth should be managed as early as possible. The present case report highlights the orthodontic traction of the impacted maxillary central incisor caused by a supernumerary tooth. At the same time, the treatment outcome regained smile in an 11-year-old patient who had stopped smiling because his peers had started to call him by the name “toothless”.